DYNAMIC VISUALIZATION AND CALCULATION OF STRESSES DURING BENDING AND TORSIONAL LOADING - FILÍPEK, Josef; NAVRÁTIL, Miroslav (Trends in education, 2009)
The paper uses animation to show the course of normal tension of a bent girder and shear tension of a twisted rod. For the derivation of strength equations with the use of high mathematics a number of idealized assumptions must be applied. The authors endeavour to show that even relatively complicated technical problems can be presented clearly and comprehensibly to students.
Keywords: flexion and torsion; normal and shear tension; cross-section module; animated presentations.